Middle Child: Communication Dynamics In The Movie A Long Way To Come Home - Frahmadan Almer; Asyandika Alfian; Aghnia Dian Lestari (CV. AFDIFAL MAJU BERKAH, 2025)
Every child has unique characteristics, especially the middle child. Middle children bring their own challenges, they have to balance the desire to be noticed with the role as a mediator. The researcher examines more deeply the communication dynamics of middle children in the movie “Jalan yang Jauh Jangan Lupa Pulang” (A Long Way To Come Home). This research aims to reveal the communication dynamics of middle children in families, friendships, and couples using Roland Barthes' semiotic approach. Through qualitative methods involving observation and interviews, this research reveals the denotation, connotation, and mythical meanings related to the role of middle children in the family. The results of the analysis show that good family communication is essential for building the middle child's self-confidence, while a lack of attention can lead to feelings of alienation and emotional conflict. In addition, this study also explores the communication dynamics of friendship and couple relationships, emphasizing that jealousy and distrust can damage interpersonal relationships. The importance of even-handed attention from the family to prevent negative impacts on the emotional development of the middle child, as well as the importance of effective communication in all aspects of the relationship, are discussed